Association of serum uric acid and metabolic syndrome among health personnel from a public hospital in Peru - Galindo Yllu, Brenda Mireya (2021)
We explored the association between serum uric acid (SUA) to metabolic syndrome (MetS) and insulin resistance (IR) among health personnel from a public hospital in Peru in a cross-sectional study with data from the Plan for the Prevention and Surveillance of Communicable and Non-Communicable Diseases of Huaycán Hospital. MetS was defined according to Latin American Diabetes Association (ALAD) criteria and IR with surrogate IR markers, triglycerides to HDL-C ratio (TG/HDL-C), and triglycerides to glucose index (TyG). The association between SUA to MetS and IR was determined using Poisson regression models in a sample of 292 participants with an average age of 46.2 ± 10.6 years. The total prevalence of MetS was 38% and the adjusted regression models showed that women with SUA in the high tertile increased the prevalence of MetS (aRP:1.71, 95%CI: 1.07 – 2.74), hypertriglyceridemia (aRP:2.02, 95%CI: 1.13 – 3.62) and elevated TyG (aRP:1.90, 95%CI: 1.12 – 3.21) compared to low tertile of SUA. We concluded that SUA is stronger associated with MetS and IR in women than the overall population of health personnel. On the other hand, more research is required and lifestyle interventions to control risk factors to MetS and IR in women.